Anatomical and morphometric variants of anterior communicating artery complex and their clinical aspects - Krzyżewski, Roger (2020)
Anterior communicating artery is the most common location of intracranial aneurysms development. Anatomical and geometrical variants of its complex play an important role in that process. Aim of the study was to describe and classify anatomical variants of anterior communicating artery complex, relate them to gender and determine their correlation with risk of development and rupture of aneurysms. Following thesis is consisted of 3 articles analysing morphology of anterior communicating artery complex. First two focus on anterior communicating artery complex anatomical variants in respectively 150 and 411 patients. Another one describes analysis of anterior cerebral artery tortuosity in respectively 121 patients. Studies showed that female patients more often had anatomical variability of anterior communicating artery complex. Also, anterior communicating artery aneurysms were less common among these patients. Abnormalities in development of A1 and A2 segments increased risk of these aneurysms development and tortuosity of anterior cerebral artery - risk of its rupture.
Keywords: anterior communicating artery; anatomical variants; intracranial aneurysms